PENGEMBANGAN ATRIBUT PERHITUNGAN NILAI PERLINDUNGAN JALAN UNTUK RUAS JALAN NASIONAL INDONESIA DARI PERSPEKTIF PENGENDARA KENDARAAN BERMOTOR RODA EMPAT ATAU LEBIH - Muhammad Idris; Wimpy Santosa; Anastasia Caroline Sutandi (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
This paper presents the development of road assessment attributes for the calculating Road Protector Scores (RPS) or Star Rating Scores (SRS) model for Indonesia’s national roads derived from the perspective of four-wheeled or more motorized vehicle drivers. Based on the study of traffic accident characteristics from a total of 283,518 accidents, two new accident types are considered significant as parameters for calculating SRS. These accidents are front-rear collision and front-side collision, and they are the top of highest types of accidents on Indonesia’s national roads. The inclusion of the two types of accidents is hypothesized to provide differences between the attributes in the SRS model for Indonesia’s national roads and the SRS developed by iRAP. Benchmarking and studies based on accident characteristics of the attributes have resulted 51 items while the SRS iRAP model has 31 items. A quadrant analysis by using Importance and Performance Analysis (IPA) method, have shown that there are 43 attributes that can be divided into six parameters of the National Road SRS model. Sign test using a binomial table that has use in this research also proves that there is a significant difference between the numbers of attributes of the two road assessment attributes of SRS iRAP and SRS National Road models. The difference in attributes in the two SRS models is shown by 17 different and completely new road attributes from the previous SRS models. This result implies that the RPS attributes in the iRAP model must be modified according to the dominant types of accidents if it is to be applied in Indonesia. Theferefore, an SRS model developed for Indonesia's national roads needs to integrate these attributes.